2014
DOI: 10.7314/apjcp.2014.15.4.1611
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemopreventive Effect of Spirogyra Neglecta (Hassall) Kützing on Diethylnitrosamine-Induced Hepatocarcinogenesis in Rats

Abstract: Spirogyra neglecta, a freshwater green alga, is a local food in the northern and northeastern parts of Thailand. This investigation explored the anticarcinogenicity of S neglecta and its possible cancer chemopreventive mechanisms in rats divided into 14 groups. Groups 1 and 10 served as positive and negative control groups, respectively. Groups 1-9 were intraperitoneally injected with diethylnitrosamine (DEN) once a week for 3 weeks. Groups 10-14 received normal saline instead. One week after the last DEN inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…The avidin–biotin complex method was used to stain the hepatic GST-P positive foci ( Figure 6 A), according to the method of Thumvijit et al [ 29 ]. The number and the areas of the GST-P positive foci that were greater than 0.2 mm in diameter were determined using the LAS Interactive Measurement program.…”
Section: Methodsmentioning
confidence: 99%
“…The avidin–biotin complex method was used to stain the hepatic GST-P positive foci ( Figure 6 A), according to the method of Thumvijit et al [ 29 ]. The number and the areas of the GST-P positive foci that were greater than 0.2 mm in diameter were determined using the LAS Interactive Measurement program.…”
Section: Methodsmentioning
confidence: 99%
“…The glutathione S -transferase placental form (GST-P) positive foci were stained by the avidin–biotin complex method according to Thumvijit et al [41]. The liver tissues were deparaffinized and rehydrated with xylene and ethanol, respectively, at optimal concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Histologically, DSS-induced colitis is characterized by erosion, ulceration, submucosal infiltration of inflammatory cells and crypt loss (Wirtz et al, 2007). It is commonly believed that DSS causes direct toxicity to gut epithelial cells and abrogates the integrity of the mucosal barrier, allowing lumen bacteria into the rat liver (Thumvijit et al, 2014). Furthermore, not only different alga but also derivatives have been reported as bioactive agents (Wijesekara et al, 2011;Ngo and Kim, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As it has been found that Spirogyra neglecta mainly contains sulfated polysaccharides and chlorophyll (Thumvijit et al, 2014), we hypothesized that it could have preventive effects on DSS-induced colitis. To investigate modifying effects of SNE, polysaccharide (PE) and nonpolysaccharide (CF) fractions on DSS-induced colitis in ICR mice and to elucidate mechanisms, we performed the present histopathological analysis, evaluating alteration in cellular proliferation and apoptosis, as well as identifying differentially expressed proteins and affected upstream regulators in the colon mucosa of mice after short-term administration of DSS and test agents.…”
Section: Introductionmentioning
confidence: 99%